Towards an aggregate production function for Irish agriculture - O'Rourke, A.Desmond (Economic & Social Studies, 1978)
Much research effort has been expended in other countries in generating measures of the aggregate production function for the agricultural sector as a means of examining technological relationships between inputs and outputs, substitutability between inputs, economies of scale, optimum resource use, optimum growth paths, etc. Only one such effort has been published for Irish agriculture, that by Rasmussen with Sandilands (1962), which used data from the 1955-58 National Farm Surveys. Unfortunately, Rasmussen's study, published in 1962, pre-dated the emergence of the agricultural economics profession as a potent influence on Irish agricultural policy. (For example, the first issue of the Irish Journal of Agricultural Economics and Rural Sociology appeared only in 1967.) The small body of agricultural economic researchers were forced to devote most of their attention to specific farm management and commodity marketing problems. Accordingly, there has been no attempt to develop a more up-to-date measure of the aggregate production function for Irish agriculture. The present study applies a method proposed by Tyner and Tweeten (1965 and 1966) to Irish time series data for the years 1956-75.
Keywords: Agricultural economics - Ireland; National Farm Surveys